Association of Radial Longitudinal Deficiency and Thumb Hypoplasia: An Update Using the CoULD Registry. (21st October 2020) - Forman, Malka; Canizares, Maria F.; Bohn, Deborah; James, Michelle A.; Samora, Julie; Steinman, Suzanne; Wall, Lindley B.; Bauer, Andrea S.; Bae, Donald S; Goldfarb, Charles A; Miller, Patricia E
Abstract : Background: Deficiency of the radial aspect of the forearm and hand is the most common congenital longitudinal deficiency of the upper limb. Radial longitudinal deficiency is associated with several named syndromes. The purpose of the present study was to explore patterns of radial longitudinal deficiency and thumb hypoplasia in syndromes and to examine the severity of these differences across various syndromes. Methods: Data were collected from the Congenital Upper Limb Differences (CoULD) registry. Congenital differences are classified in the registry with use of the Oberg-Manske-Tonkin (OMT) classification system. Diagnosis of a syndrome by a physician as noted in the CoULD registry was recorded. Thumb deficiency and radial deficiency were classified according to the modified versions of the Blauth criteria and the Bayne and Klug criteria, respectively. Results: We identified 259 patients with 383 affected limbs with radial deficiency. Eighty-three of these patients had a diagnosed syndrome. The severity of radial deficiency was correlated with the severity of thumb deficiency. The Kendall tau coefficient indicated significant correlation between radial severity and thumb severity (tau = 0.49 [95% confidence interval = 0.40 to 0.57]; p < 0.05). Subjects with a syndrome were twice as likely to have bilateral deficiency and 2.5 times more likely to have both radial and thumb deficiency compared with subjects without a syndrome. Subjects with VACTERL syndrome (vertebral defects, anal atresia, cardiac anomalies, tracheoesophageal fistula, renal anomalies, and limb defects) had patterns of thumb and radial deficiency similar to the general cohort, whereas subjects with Holt-Oram syndrome, TAR (thrombocytopenia absent radius) syndrome, and Fanconi anemia demonstrated varied presentations of thumb and radial deficiency. Conclusions: The present study investigated the characteristics of patients with radial longitudinal deficiency and thumb hypoplasia. Our results support the findings of previous research correlating the severity of radial deficiency with the severity of thumb deficiency. Furthermore, we identified characteristic features of patients with radial longitudinal deficiency and associated syndromes.